2017
DOI: 10.1007/978-3-319-65527-7_2
|View full text |Cite
|
Sign up to set email alerts
|

A Practice-Based Approach to Safety as an Emergent Competence

Abstract: This chapter proposes to look at safety as a collective knowledgeable doing, i.e. a competency embedded in working practices. Therefore, by adopting a practice-based approach to inquire into how work is actually accomplished, we can study how knowing safe and safer working practices is kept and maintained within situated ways of working and talking about safety. The knowledge object 'safety' is constructed-materially and discursively-by a plurality of professional communities, according to specific scientific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 17 publications
(14 reference statements)
1
19
0
Order By: Relevance
“…This collective understanding enables decision-making processes based on negotiation, causing changes in the practices, aiming at the preservation of life, the environment, and production. That is, in this context, there are signs that safety is an emergent competence that is performed in practice, that is socially built and communicated to the new members of this community, and that is embedded in values, norms, and social institutions (Gherardi, 2018). Besides, it also evinces what is discussed by Gherardi and Nicolini (2002) about not learning safety but work safety practices.…”
Section: The Discussion About the Sustainability Learning Process And Knowledge-in-practicementioning
confidence: 88%
See 1 more Smart Citation
“…This collective understanding enables decision-making processes based on negotiation, causing changes in the practices, aiming at the preservation of life, the environment, and production. That is, in this context, there are signs that safety is an emergent competence that is performed in practice, that is socially built and communicated to the new members of this community, and that is embedded in values, norms, and social institutions (Gherardi, 2018). Besides, it also evinces what is discussed by Gherardi and Nicolini (2002) about not learning safety but work safety practices.…”
Section: The Discussion About the Sustainability Learning Process And Knowledge-in-practicementioning
confidence: 88%
“…All those practices seem to indicate a recurring narrative that, in this working context, there has been a change in the communication flow, in the volume and in the quality of information, with the increase of the participation of the people and that all that allows the group to organize itself around the "knowing how we go" (Gherardi, 2018). The larger participation of these operators suggests a disruption of a mechanistic logic that predominated in this organization, in which the operator was not a thinking being but rather a labor force whose most privileged characteristic was the physical strength and the repetition capacity.…”
Section: The Discussion About the Sustainability Learning Process And Knowledge-in-practicementioning
confidence: 99%
“…By focusing on the occupational dimension, our approach is in line with the practice-based view of safety and reliability (Gherardi, 2018;Gherardi & Nicolini, 2000;Tillement et al, 2009). Through the practice lens, safety and resilience are seen as a "collective knowledgeable doing [that emerges] from the working practices of a community" (Gherardi, 2018, p. 12).…”
Section: Coordination Between Occupational Groups As a Source Of Project Resiliencementioning
confidence: 99%
“…We then demonstrate that resilience is also built at an occupational level. Adopting an occupational lens (Brown & Duguid, 1991;Gherardi, 2018) shows the extent to which resilience, seen as the situated ability to anticipate and adapt to safety issues, is embedded in a long-term trajectory. The occupation thus appears to enable the existence of a common set of values and principles around which workers belonging to various companies and working under different contracts can come together.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, looking at the debate and theory development in safety studies, we observed that the relatively few studies addressing this link were quantitative, rather static and distant from work situations and emerging and evolving collective practices. This is surprising given the recent developments of practice-based approaches in the field of safety [4,5]. As such, we perceived that there is a need for research that is more empirically grounded, reflecting on and through practices, beneficial to both academics and practitioners and resulting from close collaborations between these actors.…”
Section: Introductionmentioning
confidence: 97%